Semtest, Inc. a methods study - Crisostomo, Catherine Q.; Leung, Vincent Charles P.; Reidenbach, Kathryn Rose D.; Villar, Maria Zenaida P.; Virola, Henry Rophen B. Jr. (Diliman, Quezon City College of Engineering, 1991)
A methods study was conducted in the Printed Circuit Board Fabrication Department of SEMTEST, INC. The study was limited to the fabrication of the Trailer Light Interface System printed circuit boards, a standard product line of the said company. The study covered the process starting from the issuance of raw paper epoxy FR-3 boards until storage of the printed circuit boards, ready for assembly. In conducting the study the entire procedure of producing the boards were taken into consideration, inclusive of the various sub-operations involved. The work area and work environment were similarly covered. The proposed changes include the restructuring of the layout, and a number of equipment modifications and improvements, safety factors, addition of fixtures, and improvements on selected methods of procedure. These improvements and modifications were proposed to enhance and increase efficiency of printed circuit board manufacturing.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Semtest Incorporated; Systems analysis